Methodical manual with practical training Topic 1 : Forensic medical examination of mechanical asphyxia. Topic 2 : Forensic examination of injuries and death from action of physical factors: extreme temperatures, electric current, barometric pressure, and ionizing radiation : for foreign students of medical and pediatric faculties - Tumanskiy, V. A.; Tumanskaya, L. M.; Туманський, Валерій Олексійович; Туманська, Любов Михайлівна (Запорізький державний медичний університет, 2017)
The methodical manual are made by professor Tumanskiy V.A. and associate professorTumanskaya L. M. on the basis of the textbook “Babanin A. A., Belovitsky O. V., Skrebkova O. Yu. Forensic medicine. - Simferopol, 2007” and the textbook “The synopsis of Forensic medicine and toxicology” by Dr. K. S. Narayan Reddy 2014. The methodical manual are assigned for the students of 4-th course of medical and pediatric faculties for the active study and optimum learning forensic medicine in the Zaporozhye State medical University in accordance with the requirements of «Program of the forensic medicine».